Much Ado about Disinformation: A Critical Approach to Coping with Information Manipulation in a Post-Truth World - Seo, Dong-ha (Scientia Militaria - South African Journal of Military Studies, 2024)
The purpose of the study on which this article is based, was to explore how to build cadets’ ability to fight against disinformation in a post-truth age. Considering lessons from the study of the human mind, invited us to examine why we fail to discern truths rather than how to win this fight. Disinformation – often interchangeably called “fake news” – seeks to shape or change perceptions of information users. The understanding of disinformation by our young leaders is crucial because it – i.e. sowing distrust and doubt among members – is dangerous and even fatal to the Army, which places great emphasis on mutual trust as its core value. The military in general and the Army in particular are expanding their information operations capabilities, as North Korea is one of the few countries that actively engage in a disinformation campaign. During their years at the military academy, cadets should however improve their ability to discern truths before acquiring skills relevant to a counter-disinformation campaign. The best way to enhance cadets’ ability to discern truths – even in a media-saturated age – is still to participate in deep reading, especially reading imaginative literature that fosters inventive as well as critical thinking. The current study argued that our grasp of human frailty through deep reading helps us develop an ability to discern truths.